Ultra-thin film sensors based on porphyrin-5-ylphosphonate diesters for selective and sensitive dual-channel optical detection of mercury(II) ions. (February 2021) - Ermakova, Elizaveta V.; Koroleva, Elena O.; Shokurov, Alexander V.; Arslanov, Vladimir V.; Bessmertnykh-Lemeune, Alla
Abstract: Reusable dual-channel optical sensors for Hg 2+ ions were prepared by Langmuir-Schaefer (LS) method from amphiphilic ( trans -A2 )BC-type porphyrins functionalized at meso- positions of the tetrapyrrolic macrocycle by sterically demanding diethoxyphosphoryl and mesityl groups as well as electron donating RO, RS or RNH substituents (R =  n -C8 H17 ). These three novel amphiphilic porphyrin derivatives were synthesized in good yields and their floating films at the air⎯water interface were investigated. In these monolayers, porphyrin molecules display a slipped stack-of-card orientation, but their strong π stacking is prohibited by bulky diethoxyphosphoryl and mesityl groups. The heteroatom substituent plays a key role in the molecular organization of the monolayers because it can participate in intermolecular hydrogen bonding, which influences the monolayer structure. Sensing properties of the porphyrins organized in Langmuir monolayers differ from those in the solution environment. Selective spectrophotometric detection of Hg 2+ ions by these floating films is observed because interfering Cu 2+, Zn 2+, Cd 2+, and Pb 2+ ions are coordinated to donor centers located at the periphery of the macrocycle. Transfer of these floating films onto a polyvinyl chloride surface by LS technique affords perforated multilayer films with a tight molecular coverage of the solid support. The effect of the heteroatoms on the organization of these films was demonstrated by scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). Both absorption and emission studies provide a strong evidence that chromophore-chromophore interactions are rather weak in these LS films. Binding of mercury(II) ions by the films and the regeneration of the sensors were explored visually and using reflection absorbance and fluorescence spectroscopies and then confirmed by X-ray fluorescence analysis. Detection limit of these selective and reusable dual-channel (absorbance and fluorescence) thin-film sensors is about 10 −8  M (2 ppb), that corresponds to the action level for Hg 2+ ions in drinking water recommended by the U.S. Environmental Protection Agency (EPA). Graphical abstract: Image 1 Highlights: Porphyrin-based reusable dual-channel (absorbance/emission) sensors for Hg 2+ were prepared by Langmuir-Schaefer technique. The structure of synthesized porphyrins was tuned to form stable non-aggregated films. Detection limit of Hg 2+ ions in aqueous media by thin-film sensors was 2 ppb. Sensing properties of LS films remarkably differ from those of their molecular precursors and cast films.